2007
DOI: 10.1002/pbc.20687
|View full text |Cite
|
Sign up to set email alerts
|

Autologous transplantation of CD133 selected hematopoietic progenitor cells for treatment of relapsed acute lymphoblastic leukemia

Abstract: A 21-year-old white male with relapsed acute lymphoblastic leukemia (ALL) developed an invasive Zygomycosis infection 3 weeks after beginning re-induction chemotherapy. Because of the high risk of fatal recurrence of the fungal infection, neither long-term maintenance chemotherapy nor allogeneic hematopoietic stem cell transplant (HSCT) was considered appropriate. Because his ALL blasts expressed CD34 but lacked CD133, he received a CD133 selected autologous graft following high-dose consolidation chemotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Several approaches have been adopted to improve the quality of life and to increase the life expectancy of patients with hematological malignancies. Different methods of HSC therapy are found to be beneficial in leukemic patients [169-171]. …”
Section: Clinical Applications Of Hscmentioning
confidence: 99%
“…Several approaches have been adopted to improve the quality of life and to increase the life expectancy of patients with hematological malignancies. Different methods of HSC therapy are found to be beneficial in leukemic patients [169-171]. …”
Section: Clinical Applications Of Hscmentioning
confidence: 99%
“…1) [11,16,79,81,87,88,90]. More specifically, HSC transplants, alone or in combination therapy, may be used for the treatment of patients with autoimmune diseases, refractory and severe aplastic anemias, congenital thrombocytopenia, osteoporosis, cardiovascular disorders, chronic inflammatory Bowel disorders (IBD) including Crohn's disease and ulcerative colitis, diabetes mellitus, leukemias, multiple myelanomas and Hodgkin's and non-Hodgkin's lymphomas and aggressive tumors [1,2,11,16,[57][58][59][60][93][94][95][96][97]. It has also been reported that MSCs, EPCs and their progenies can contribute to the regenerative process of several tissues including bone, cartilage, tendon, muscle, adipose, brain, lung, heart, pancreas, kidney and eye [98,99].…”
Section: Therapeutic Applications Of Bm-derived Stem/progenitor Cellsmentioning
confidence: 99%
“…Among them, there are leukemias, multiple myeloma, Hodgkin's and non- Hodgkin's lymphomas, melanoma and aggressive and metastatic solid tumors such as sarcomas, retinoblastoma, kidney, brain, lung, pancreatic, prostate, breast and ovarian cancers. 9-11,19,41,42 In fact, HSC transplant may restore the hematopoietic and immune systems after myeloablative effects induced by high-dose irradiation or chemotherapy following a treatment of cancer patients (Fig. 2).…”
Section: Bone Marrow-derived Stem/progenitor Cells and Their Therapeumentioning
confidence: 99%
“…For instance, the autologous transplantation of CD133 + selected HSCs may be used for pediatric patients with relapsed CD34 + /CD133 - leukemia. 42 The results from a recent investigation have also revealed that the homing and engraftment of BCR-ABL + leukemic stem cells (LSCs) in the BM of patients with chronic myelogenous leukemias (CMLs) is highly dependent on CD44 adhesion molecule expression in respect to normal HSCs. 46 Therefore, the targeting of CD44 LSC using an anti-CD44 antibody also may constitute an alternative approach for improving the efficacy of HSC transplantation in CML patients.…”
Section: Bone Marrow-derived Stem/progenitor Cells and Their Therapeumentioning
confidence: 99%